Evaluation of the intraocular total IgE level and its ratio with serum IgE level for the diagnosis of ocular toxocariasis in children and adults: a retrospective comparative study - Shuang Zhang; Li Chen; Xiaofeng Hu; Hui Wang; Jing Feng; Yong Tao (BMC Ophthalmology)
Abstract Background Ocular Toxocariasis (OT) is characterized by complicated clinical manifestations, which makes it difficult to diagnose. In this study, we mainly evaluated the diagnostic values of intraocular fluid (IF) total IgE level and IF/Serum IgE ratio in OT and compared the differences between child and adult patients. Methods 76 patients with 52 children (< 16 years) and 24 adults of clinically-diagnosed OT and 64 patients with non-OT uveitis were enrolled in this study. The paired IF and serum samples were collected for total IgE, total IgG and specific IgG testing. The IF IgE levels and IF/Serum IgE ratios were compared between child and adult patients. The area under the curve (AUC) was generated to assess the diagnostic performances of the above indicators. Results The IF IgE level was significantly higher in child patients than in adult patients (1671.79 ± 1425.97 versus 784.44 ± 544.73 ng/ml, p = 0.015). Besides, the IF/Serum IgE ratio showed similar trend with 24.02 ± 6.10 in children and 7.68 ± 5.05 in adults (p = 0.001). The best cutoff value of the IF IgE concentration was 10.65 ng/ml, yielding 77.6% (95%CI, Confidence Interval, 66.4–86.1%) sensitivity and 98.4% (95%CI, 90.5–99.9%) specificity. The IF IgE level showed lower AUC than that of IF specific IgG level (0.925 versus 0.975, p = 0.037). However, the AUC of IF/Serum IgE ratio for OT was significantly higher than that of GWC (0.934 versus 0.527, p < 0.0001). The best cutoff value of IF/Serum IgE ratio was 0.48 with the sensitivity of 78.4% (95%CI, 67.0-86.8%) and specificity of 98.4% (95%CI, 90.5–99.9%). For the diagnosis of child OT, the cutoff value of IF IgE level of child OT was 13.10 ng/ml with the high sensitivity of 82.7% (95%CI, 69.2–91.3%) while the best cutoff value of 10.65 ng/ml for adult OT yielded only 66.7% (95%CI, 44.7–83.6%) sensitivity. However, the sensitivity of IF/Serum IgE ratio for child OT (86.3%, 95%CI, 73.1–93.8%) was close to that for adult OT (87.0%, 95%CI, 65.3–96.6%). Conclusions Both IF IgE level and IF/Serum IgE ratio demonstrated good diagnostic performance for ocular toxocariasis and higher sensitivity of IF IgE level was noted for the diagnosis of child OT.